2020
DOI: 10.1029/2019jd030619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evaporation Climatology for the Congo Basin Wet Seasons in 11 Global Climate Models

Abstract: Across the Congo, there is a wide spread in rainfall in the two wet seasons in Coupled Model Intercomparison Project 5 global climate models (GCMs). As the Congo is believed to be a moisture recycling hot spot, the evaporation of excess water from the land surface in some models could be amplifying the model spread in rainfall. This study performs an exploratory process‐based evaluation of Congo Basin evaporation in 11 Coupled Model Intercomparison Project 5 GCMs that took part in the Atmospheric Model Interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 103 publications
2
13
0
Order By: Relevance
“…This suggests that rainfall amounts on the basin-wide average are similar in March and November. Crowhurst et al (2020) also found that the best performing GCMs with low root mean square errors against LandFlux-EVAL evaporation reference data (Mueller et al 2013) have lower evaporation in November than March on the basin-wide average, which agrees with several reanalyses (Fig. 1b, Table 1).…”
Section: Lower Evaporation In November Than March In the Congo Basinsupporting
confidence: 86%
See 3 more Smart Citations
“…This suggests that rainfall amounts on the basin-wide average are similar in March and November. Crowhurst et al (2020) also found that the best performing GCMs with low root mean square errors against LandFlux-EVAL evaporation reference data (Mueller et al 2013) have lower evaporation in November than March on the basin-wide average, which agrees with several reanalyses (Fig. 1b, Table 1).…”
Section: Lower Evaporation In November Than March In the Congo Basinsupporting
confidence: 86%
“…To find out why evaporation is lower in November than March on the basin-wide average, and to begin understanding the controls on the seasonal cycle of basin evaporation, this study will first need to identify where in the basin evaporation is lower in November than March, and then discover which evaporation components are responsible in these regions separately. Crowhurst et al (2020) found that on the basin-wide average, the best performing GCMs have similar canopy evaporation and soil evaporation in March and November, but lower transpiration in November than March. The authors therefore argued that lower transpiration is likely to explain why evaporation is lower in November than March on the basin-wide average.…”
Section: Lower Evaporation In November Than March In the Congo Basinmentioning
confidence: 95%
See 2 more Smart Citations
“…While some previous studies have applied a similar technique to the Congo Basin as part of larger-scale experiments, these studies assumed terrestrial water storage was constant over their study periods (Marshall et al, 2012;Ukkola and Prentice, 2013;Weerasinghe et al, 2020) -a plausible assumption for long-term ET estimates but one that could mask a large degree of ET variability on annual and shorter timescales. Indeed, remotely sensed evidence suggests water storage anomalies within the basin do change significantly on monthly and interannual timescales (Crowley et al, 2006;Rodell et al, 2018), even if long-term trends are typically small relative to the magnitude of ET fluxes (Weerasinghe et al, 2020). Thus in order to explore seasonal cycles and variations in basin-wide ET, terrestrial water storage must be constrained in inverted-water-balance models.…”
Section: Introductionmentioning
confidence: 99%